Culturally-relevant augmented user interfaces for illiterate and semi-literate users - Gavaza, Takayedzwa (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
This thesis discusses guidelines for developers of Augmented User Interfaces that can be used by illiterate and semi-literate users. To discover how illiterate and semi-literate users intuitively understand interaction with a computer, a series of Wizard of Oz experiments were conducted. In the first Wizard of Oz study, users were presented with a standard desktop computer, fitted with a number of input devices to determine how they assume interaction should occur. This study found that the users preferred the use of speech and gestures which mirrored findings from other researchers. The study also found that users struggled to understand the tab metaphor which is used frequently in applications. From these findings, a localised culturally-relevant tab interface was developed to determine the feasibility of localised Graphical User Interface components. A second study was undertaken to compare the localised tab interface with the traditional tabbed interface. This study collected both quantitative and qualitative data from the participants. It found that users could interact with a localised tabbed interface faster and more accurately than with the traditional counterparts. More importantly, users stated that they intuitively understood the localised interface component, whereas they did not understand the traditional tab metaphor. These user studies have shown that the use of self-explanatory animations, video feedback, localised tabbed interface metaphors and voice output have a positive impact on enabling illiterate and semi-literate users to access information.,TeX,Adobe Acrobat 9.51 Paper Capture Plug-in
Keywords: User interfaces (Computer systems) -- Research; Computer software -- Research; Graphical user interfaces (Computer systems) -- Research; Human-computer interaction; Computers and literacy